Histochemical investigation of Cochlospermum regium (Schrank) Pilg. leaves and chemical composition of its essential oil - Inacio, Marielle Cascaes [UNESP]; Paz, Tiago Antunes [UNESP]; Bertoni, Bianca Waleria; Ribeiro Vieira, Maria Aparecida [UNESP]; Mayo Marques, Marcia Ortiz; Soares Pereira, Ana Maria (Taylor & Francis Ltd, 2014)
Essential oil from Cochlospermum regium (Schrank) Pilg. leaves (CR-EO) has been extracted by hydrodistillation; we analysed the CR-EO by gas chromatography coupled with mass spectrometry. We also conducted histochemical analysis on cross-sections of the central vein of young and adult leaves. A total of 32 compounds were qualitatively and quantitatively analysed, which represented 94.87% of the total CR-EO oil content. The CR-EO basically consisted of sesquiterpenes (96.87%); its main component was beta-copaen-4-alpha-ol (18.73%), followed by viridiflorol (12.67%). The histochemical analyses identified the main classes of compounds present in both young and adult leaves.
Keywords: Cochlospermum regium; beta-copaen-4-alpha-ol; Bixaceae; GC-MS analysis; sesquiterpenes